Combined creatine and HMB co-supplementation improves functional strength independent of muscle mass in physically active older adults: a randomized crossover trial - Ramos-Hernández, Rafael; Miguel-Ortega, Álvaro; Martínez-Ferrán, María; Fernández-Lázaro, Diego; Busto, Natalia; Mielgo-Ayuso, Juan (Springer, 2025)
Sarcopenia is a major contributor to frailty and functional decline among older adults. Combining exercise with nutritional strategies such as creatine monohydrate (CRE) and ¿-hydroxy-¿-methylbutyrate (HMB) supplementation may help to preserve strength and independence. To evaluate the effects of 6-week CRE + HMB supplementation combined with an integral physical conditioning (IPC) program on functional strength and body composition in physically active older adults. In a randomized, double-blind, placebo-controlled crossover trial, 30 older adults (20 men, 10 women; ¿ 60 years) completed two 6-week intervention periods (CRE + HMB or placebo) separated by a 3-week washout. The IPC program performed in both conditions consisted of four supervised weekly sessions combining strength, power, multicomponent circuits, high-intensity interval and moderate intensity continuous training), performed at 40-100% training heart rate (THR) and 20-90% one-repetition maximum (1RM) and structured as warm-up, main part and cooldown. Functional strength and body composition (bioelectrical impedance analysis) were assessed pre- and post-intervention, respectively. Significant time × group interactions were observed for fat mass, fat-free mass, total muscle mass, skeletal muscle mass, appendicular skeletal muscle mass, muscle mass index, skeletal muscle index and ALM/BMI (all p < 0.05). The CRE + HMB group showed reductions in fat mass and body fat percentage, with slight numerical increases in muscle parameters, whereas the placebo group exhibited opposite trends. However, within-group changes were not statistically significant. In contrast, CRE + HMB significantly improved multiple functional strength outcomes, including leg/back strength, arm flexion strength, upper-body endurance (dumbbell flexion, push-ups, isometric hold) and core endurance (crunches). Regression analyses suggested that these improvements were largely independent of changes in muscle mass, supporting a potential neuromuscular mechanism. Six weeks of CRE + HMB supplementation combined with IPC enhanced functional strength and endurance in active older adults, largely independent of changes in muscle mass. This combined approach represents a promising strategy for preserving functional capacity and promoting healthy ageing.